Organic solid-state lasers: a materials view and future development - Jiang, Yi; Liu, Yuan-Yuan; Liu, Xu; Lin, He; Gao, Kun; Lai, Wen-Yong; Huang, Wei (Chemical Society reviews, 2020)
Lasing applications have spread over various aspects of human life. To meet the developing trends of the laser industry towards being miniature, portable, and highly integrated, new laser technologies are in urgent demand. Organic semiconductors are promising gain medium candidates for novel laser devices, due to their convenient processing techniques, ease of spectral and chemical tuning, low refractive indexes, mechanical flexibilities, and low thresholds, etc. organic solid-state lasers (OSSLs) open up a new horizon of simple, low-cost, time-saving, versatile and environmental-friendly manufacturing technologies for new and desirable laser structures (micro-, asymmetric, flexible, etc. ) to unleash the full potential of semiconductor lasers for future electronics. Besides the development of optical feedback structures, the design and synthesis of robust organic gain media is critical as a vigorous aspect of OSSLs. Herein, we provide a comprehensive review of recent advances in organic gain materials, mainly focused on organic semiconductors for OSSLs. The significant breakthroughs toward electrical pumping of OSSLs are emphasized. Opportunities, challenges and future research directions for the design of organic gain media are also discussed. This review introduces the design, opportunities, and challenges of organic gain media for organic solid-state lasers, especially for organic semiconductor lasers, providing a clear panorama for this interesting and exciting research field.